The college admissions contribution to the labor market beauty premium. (Contemporary Economic Policy, 2022)
We investigate the contribution of college admissions to the labor market beauty premium. We sampled 1800 social media profiles of students from universities ranked from 1 to 200 in China and the US. Chinese universities use standardized test scores for admissions. US universities use also extracurricular activities. Consistent with beauty‐blind admissions, alumni's beauty is uncorrelated with the rank of the school they attended in China. In the US, White men who attended high‐ranked schools are better looking, especially attendees of private schools. A one percentage point increase in beauty rank corresponds to a half‐point increase in the school rank.